Unsophisticated Arbitrageurs and Market Efficiency: Overreacting to a History of Underreaction? - MILIAN, JONATHAN A. (Journal of Accounting Research, 2015)
ABSTRACT Prior research has documented that arbitrage activity significantly reduces or eliminates stock market anomalies. However, if anomalies arise due to unsophisticated investors’ behavioral biases, then these same biases can also apply to unsophisticated arbitrageurs and thereby disrupt the arbitrage process. Consistent with a disruption in the arbitrage process for the post‐earnings announcement drift anomaly, I document that the historically positive autocorrelation in firms’ earnings announcement news has become significantly negative for firms with active exchange‐traded options. For these easy‐to‐arbitrage firms, the firms in the highest decile of prior earnings announcement abnormal return (prior earnings surprise), on average, underperform the firms in the lowest decile by 1.59% (1.43%) at their next earnings announcement. Additional analyses are consistent with investors learning about the post‐earnings announcement drift anomaly and overcompensating. This study suggests that unsophisticated attempts to profit from a well‐known anomaly can significantly reverse a previously documented stock return pattern.